2011
DOI: 10.1210/jc.2010-2310
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Stretch and Progesterone Action

Abstract: These data show that progesterone does not inhibit stretch-induced MAPK activation or gene expression, possibly explaining why progesterone is ineffective in the prevention of preterm labor in multiple pregnancy. Although stretch did reduce progesterone receptor expression in a nuclear factor κB-dependent manner, this was not sufficient to inhibit progesterone action, suggesting that it is not responsible for the functional progesterone withdrawal observed with the onset of human labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
(46 reference statements)
3
30
1
1
Order By: Relevance
“…We found that constant stretch, applied by means of hanging 1 or 3 g weights from tissue strips, had no effect on culture-induced changes in PR isoform expression (Figure 4). This is inconsistent with a previous report where stretch downregulated PR-T and PR-B expression; however, it should be noted that those studies used myometrial cells while our study uses myometrial tissue strips [56]. Previous animal studies suggest that progesterone is responsible for maintaining uterine quiescence and promoting myometrial hyperplasia and hypertrophy to inhibit any increase in uterine wall tension [5760].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…We found that constant stretch, applied by means of hanging 1 or 3 g weights from tissue strips, had no effect on culture-induced changes in PR isoform expression (Figure 4). This is inconsistent with a previous report where stretch downregulated PR-T and PR-B expression; however, it should be noted that those studies used myometrial cells while our study uses myometrial tissue strips [56]. Previous animal studies suggest that progesterone is responsible for maintaining uterine quiescence and promoting myometrial hyperplasia and hypertrophy to inhibit any increase in uterine wall tension [5760].…”
Section: Discussioncontrasting
confidence: 85%
“…A previous study using term nonlaboring human myometrium tissue showed that stretch applied to myometrial cells in culture resulted in decreased PR-T and PR-B mRNA expression [56]. We found that constant stretch, applied by means of hanging 1 or 3 g weights from tissue strips, had no effect on culture-induced changes in PR isoform expression (Figure 4).…”
Section: Discussionmentioning
confidence: 58%
“…We postulate that the changes in intrauterine environment (endocrine changes, for example, progesterone[29]) and mechanical factors (e.g. stretching as gestation progresses [21, 30, 31]), among others can potentially contribute to activation of stress associated p38MAPK. This then promotes the aging of the fetal tissues, thus preparing them for delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important study has revealed that women receiving 17-alpha-hydroxyl-progestrone-caproate prophylaxis before 27 weeks' gestation might have even an increased risk for preterm labor (34). Furthermore, it should be kept in mind that progesterone has no role in the prevention of preterm labor in twin pregnancy (35, 36) weekly injections of 17-alpha-hydroxyl-progestrone-caproate as well as vaginal progesterone suppositories can lead to a significant reduction in the rate of recurrent preterm labor among women who had treated with tocolytics to suppress the acute phase and also there is a considerable reduction in the neonatal complications. However, it seems that further future studies are needed to accurately define the mechanism of action of progesterone drugs in the prevention of preterm labor and to establish the optimal formulation, route of administration, dose, and gestational age at initiation.…”
Section: Discussionmentioning
confidence: 99%